Health activism against barriers to indigenous health in Aotearoa New Zealand. Issue 4 (8th August 2017) - Came, H. A.; McCreanor, T.; Simpson, T.
Abstract: Racism and government policies of colonisation and assimilation contribute to the disproportionate burden of disease carried by indigenous people globally. In colonial contexts such as Aotearoa New Zealand, these inequities are routinely monitored but governments believe economic growth and better lifestyles will resolve the issues. Stop Institutional Racism (STIR), a group of health activists, is challenging this dominant discourse and building a boutique social movement to transform racism within the New Zealand public health sector. Central to the work of STIR is partnership between indigenous and non-indigenous practitioners underpinned by Te Tiriti o Waitangi – the founding document of the colonial state of New Zealand. This paper reflects on STIR organisational processes and political achievements to date. We have worked towards mobilising the public health sector, re-energising the conversation around racism and strengthening the capacity and evidence base of the sector around key sites of racism and anti-racism praxis. This paper will be of interest to others within the global public health community who are looking for new collective ways to organise and challenge entrenched inequities.